Leadership for the team physician - Tayne, S.; Hutchinson, M. R.; O'Connor, F. G.; Taylor, D. C.; Musahl, V.; Indelicato, P. (Current Sports Medicine Reports, 2020)
Physician leadership of the interdisciplinary sports medicine team depends on fundamental leadership skills that often are overlooked in medical school. These leadership skills include effective communication, emotional intelligence, teamwork, selfless service, integrity, and critical thinking while utilizing an athlete-centered approach. Development of these skills will help to navigate team management and important decisions, such as return to play. The leadership session at the Advanced Team Physician Course sought to acknowledge the gap in medical training regarding leadership education and began to address it in a forum specifically for team physicians. Here we provide a summary of the lectures and presentations from the 2018 Advanced Team Physician Course in an effort to benefit a broader physician audience. Thismaterial should act as a framework for current and future team physicians to solidify their role as the leader of the medical team in caring for the athlete.